Confinement‐driven cocrystallization of binary polymer mixtures of different chain length in electrospun nanofibers. Issue 3 (27th August 2018) - Samanta, Pratick; Srivastava, Rajiv; Nandan, Bhanu
Abstract: The effect of molecular weight on the crystallization behavior of poly(ethylene oxide) (PEO) confined in the glassy polystyrene (PS) matrix in electrospun nanofibers of PS/PEO blends were investigated. It was found that, irrespective of the PEO molecular weight, the crystallization behavior was fractionated when the weight fraction of PEO ( w PEO ) in the blend was 0.2, whereas purely homogeneous nucleated crystallization was observed when the w PEO ~ 0.1. Nevertheless, the nature of homogeneous nucleated crystallization was found to be significantly affected for very low molecular weight PEO in the blend nanofibers. The peak temperature of homogeneous nucleated crystallization was observed to shift to high supercoolings when the PEO molecular weight was decreased, and the effect was most pronounced for PEO with lowest molecular weight, that is, M PEO ~ 4000 g/mol. Furthermore, relaxation of PEO domains by thermally annealing the nanofibers above the glass transition temperature of PS resulted in an increased polydispersity in the PEO domain size when the PEO molecular weight was 4000 g/mol. This evidently led to the observation of dual homogeneous nucleated crystallization peaks which was not observed in blend nanofibers composed from PEO with M PEO ≥ 35 000 g/mol. The confinement was also found to impose a higher degree of mobility frustration on longer polymer chains such that the depression in the degree of crystallinity was significantly higher for high molecular weight PEO in the blend nanofibers. Furthermore, in the case of blend nanofibers containing mixture of two PEO with different molecular weights, the crystallization behavior was closely related to the dominant nucleation mechanism. Hence, in the case of blend nanofibers where the heterogeneous nucleation was the dominating crystallization mechanism, two melting peaks where observed revealing phase segregated crystallization behavior. However, the blend nanofibers which crystallized solely through homogeneous nucleation mechanism, the mixture of PEO fractions were found to cocrystallize as revealed from the observation of single melting peak. The cocrystallization was observed irrespective of the crystallization conditions and plausibly was a result of mobility restrictions imposed by the confinement at high degree of supercoolings. Abstract : Mixture of PEO, of two different molecular weights, were found to cocrystallize under confinement in electrospun nanofibers composed of PS/PEO blends. The cocrystallization was observed irrespective of the crystallization conditions and plausibly was a result of mobility restrictions imposed by the confinement at high degree of supercoolings. Under similar conditions, the bulk blend samples of the PEO mixtures and PS exhibited phase segregated crystallization.